Community Composition and Transcriptional Activity of Ammonia-Oxidizing Prokaryotes of Seagrass Thalassia hemprichii in Coral Reef Ecosystems - Ling, Juan; Lin, Xiancheng; Zhang, Yanying; Zhou, Weiguo; Yang, Qingsong; Lin, Liyun; Zeng, Siquan; Zhang, Ying; Wang, Cong; Ahmad, Manzoor; Long, Lijuan; Dong, Junde (Frontiers in Microbiology, 2018)
Seagrasses in coral reef ecosystems play important ecological roles by enhancing coral reef resilience under ocean acidification. However, seagrass primary productivity is typically constrained by limited nitrogen availability. Ammonia oxidation is an important process conducted by ammonia-oxidizing archaea (AOA) and bacteria (AOB), yet little information is available concerning the community structure and potential activity of seagrass AOA and AOB. Therefore, this study investigated the variations in the abundance, diversity and transcriptional activity of AOA and AOB at the DNA and transcript level from four sample types: the leaf, root, rhizosphere sediment and bulk sediment of seagrass Thalassia hemprichii in three coral reef ecosystems. DNA and complementary DNA (cDNA) were used to prepare clone libraries and DNA and cDNA quantitative PCR (qPCR) assays, targeting the ammonia monooxygenase-subunit (amoA) genes as biomarkers. Our results indicated that the closest relatives of the obtained archaeal and bacterial amoA gene sequences recovered from DNA and cDNA libraries mainly originated from the marine environment. Moreover, all the obtained AOB sequences belong to the Nitrosomonadales cluster. Nearly all the AOA communities exhibited higher diversity than the AOB communities at the DNA level, but the qPCR data demonstrated that the abundances of AOB communities were higher than that of AOA communities based on both DNA and RNA transcripts. Collectively, most of the samples shared greater community composition similarity with samples from the same location rather than sample type. Furthermore, the abundance of archaeal amoA gene in rhizosphere sediments showed significant relationships with the ammonium concentration of sediments and the nitrogen content of plant tissue (leaf and root) at the DNA level (P<0.05). Conversely, no such relationships were found for the AOB communities. This work provides new insight into the nitrogen cycle, particularly nitrification of seagrass meadows in coral reef ecosystems